FPGA Based Pattern Generation and Synchonization for High Speed Structured Light 3D Camera - Muhammad Atif; Sukhan Lee (Universitas Ahmad Dahlan, 2017)
Recently, structured light 3D imaging devices have gained a keen attention due to their potential applications to robotics, industrial manufacturing and medical imaging. Most of these applications require high 3D precision yet high speed in image capturing for hard and/or soft real time environments. This paper presents a method of high speed image capturing for structured light 3D imaging sensors with FPGA based structured light pattern generation and projector-camera synchronization. Suggested setup reduces the time for pattern projection and camera triggering to 16msec from 100msec that should be required by conventional methods.